2011
DOI: 10.1371/journal.pone.0029533
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Serum Profiling for the Discovery of Epithelial Ovarian Cancer Biomarkers

Abstract: FDA-cleared ovarian cancer biomarkers are limited to CA-125 and HE4 for monitoring and recurrence and OVA1, a multivariate panel consisting of CA-125 and four additional biomarkers, for referring patients to a specialist. Due to relatively poor performance of these tests, more accurate and broadly applicable biomarkers are needed. We evaluated the dysregulation of 259 candidate cancer markers in serum samples from 499 patients. Sera were collected prospectively at 11 monitored sites under a single well-defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 33 publications
2
41
0
2
Order By: Relevance
“…Only a few studies adopted restrictive selection criteria by excluding pregnant women,22 28 subjects with presence or previous history of cancer,19 22 28 oophorectomy26 or positive to breast cancer gene expression 32. One study included in the case group patients with low-malignant tumours potentially not detectable by biomarkers and another included in the control group only women with endometriosis 23 30.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few studies adopted restrictive selection criteria by excluding pregnant women,22 28 subjects with presence or previous history of cancer,19 22 28 oophorectomy26 or positive to breast cancer gene expression 32. One study included in the case group patients with low-malignant tumours potentially not detectable by biomarkers and another included in the control group only women with endometriosis 23 30.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies seem to adopt decision thresholds suggested by the assay manufacturer, differentiated for menopausal status only for the Architect assay. Others derived threshold values from a parallel cohort of healthy controls or from a training group,18 27 29 32 or by maximising sensitivity and specificity 28 30…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BRP-39 is secreted by cultured articular chondrocytes [15] , synovial cells [16] [Johansen, 1993 #1550], macrophages [17] , epithelial cells [18] , vascular smooth muscle cells [19] , and some cancer cells [20][21][22][23][24] . BRP-39 was identified and termed by Johansen et al in a search for new bone proteins in 1989 [25] .…”
Section: Discussionmentioning
confidence: 99%
“…In their study, a preliminary multivariate analysis, using a logistic regression model on the nine most informative biomarkers appeared to have significantly improved performance over OVA1 biomarkers. [89] Novel Therapeutics in Ovarian Carcinoma TRAP1: TRAP1 (TNF receptor-associated protein 1) is a mitochondrial heath shock protein 75 that has antioxidant and antiapoptotic functions. [90,91] It is evident that mitochondrial defects and dysfunctions of oxidative phosphorylation and energy production inovarian cancercells are directly related to their resistanceto platinum drugs.…”
Section: Tools For Risk Estimation Of Ovarian Cancermentioning
confidence: 99%